Images of Canadianness : Visions on Canada's Politics, Culture, and Economics - Leen D'Haenens
Images of Canadianness offers backgrounds and explanations for a series of relevant--if relatively new--features of Canada, from political, cultural, and economic angles. Each of its four sections contains articles written by Canadian and European experts that offer original perspectives on a variety of issues: voting patterns in English-speaking Canada and Quebec; the vitality of French-language communities outside Quebec; the Belgian and Dutch immigration waves to Canada and the resulting Dutch-language immigrant press; major transitions taking place in Nunavut; the media as a tool for self-government for Canada's First Peoples; attempts by Canadian Indians to negotiate their position in society; the Canada-US relationship; Canada's trade with the EU; and Canada's cultural policy in the light of the information highway.